First report of a spermatic granuloma and varicocele in a marsupial: A Koala (Phascolarctos cinereus) Case Study. (August 2016) - Schultz, B.K.; Palmieri, C.; Nicolson, V.; Larkin, R.; Keeley, T.; McGowan, M.; Johnston, S.D.
Abstract: This study reports the first documented clinical case of a spermatic granuloma and varicocele in a marsupial. Initial clinical presentation included gross morphological changes in the left scrotal cord, epididymis and testis. Ultrasonography of the scrotum and spermatic cord, and gross and histopathological examination after hemicastration, confirmed the condition as a spermatic granuloma affecting the left caput epididymis, with a varicocele in the left proximal spermatic cord, which was causing azoospermia and infertility. Semen quality and serum testosterone secretion following a GnRH challenge was assessed prior to, and following surgery. After hemi-castration, an increase in androgen secretion to within normal reference ranges for the koala was observed with a subsequent increase in semen production and sperm quality resulting in the sire of a pouch young, 12 months later. Highlights: First report of a spermatic granuloma and varicocele in a marsupial; the koala. Spermatic granuloma and varicocele had negatively affected androgen and spermatozoa production. Hemi-castration of the left hand side of the reproductive tract was successful. Male koala has been reintroduced into captive breeding program and has sired offspring.